Participation of ethnic minorities in natural forest management: Cat Tien National Park, Vietnam case study - Dinh Thanh Sang (Agriculture and Natural Resources, 2021)
Surveys combining in-depth interviews of households with participatory rural appraisal (PRA) were used to examine and assess the participation of ethnic minorities (EMs) in the management of natural forest resources and its impacts in Cat Tien National Park (CTNP), Vietnam. The results identified that although the sustainable development goal had not yet been achieved in CTNP, the management arrangement had succeeded in positive effects on social performance in terms of differences between participants and nonparticipants (χ2 = 30.877, p = 0.000). However, despite some positive effects, the participants faced many impediments such as a low subsidy, a long time to receive the subsidy, distrust in other participants and being sabotaged by neighbors. Based on the findings, the appropriate institutional strategies in CTNP should emphasize a reasonable subsidy to the participants and higher participation levels, social relationships and conservation awareness.